Optimalisasi Peranan Financial Technology (Fintech Sharia) Menuju Era Digitalisasi Koperasi: (Optimizing the Role of Financial Technology (FintechSharia)Towards the Cooperative Digitalization Era) - Siti Rukmana; Mustofa Mustofa (e-Journal Ekonomi Bisnis dan Akuntansi, 2022)
This study aims to find out how to optimize the role (Fintech Sharia) towards the era of cooperative digitalization. Design this research is a descriptive qualitative research. The type of data in this study uses secondary data. Sources of data were obtained through the OJK website, Bank Indonesia, books, internet, social media, laws and regulations as well as information from the Ministry of Cooperatives and SMEs RI. The research method used is library research. Cooperatives are expected to be able to compete with financial institutions such as banks. Cooperatives must also have mobile application services that offer a variety of products, both in terms of raising funds, providing financing, payment features, and purchases that can be utilized by members so that members can be loyal and able to contribute to the cooperative. Based on the definition of Fintech Lending according to OJK Legal entities or cooperatives can act as Fintech Lending providers that have a systematic application of loan transaction mechanisms online, through web websites or applications. Cooperatives should take advantage of this momentum to create financial technology applications that can be used by members and obtain permits and be registered with OJK. This financial technology momentum can make the Cooperative's strategy to increase or recruit members with the advantages of financial technology (fintech) that is trusted and does not harm members, but instead members can benefit from the distribution of the remaining operating results from the cooperative.